Impaired counterregulatory responses to hypoglycaemia following oral glucose in adults with cystic fibrosis - Aitken, Moira L. (Diabetologia, 2020)
AIMS/HYPOTHESIS: The aim of this study was to determine the mechanism(s) for hypoglycaemia occurring late following oral glucose loading in patients with cystic fibrosis (CF). METHODS: A 3 h 75 g OGTT was performed in 27 non-diabetic adults with CF who were classified based on this test as experiencing hypoglycaemia (glucose <3.3 mmol/1 with or without symptoms or glucose <3.9 mmol/1 with symptoms, n=14) or not (n=13). Beta cell function, incretin (glucagon-like peptide-1 [GLP-1] and glucose-dependent insulinotropic peptide [GIP]) and counterregulatory hormone responses (glucagon, catecholamines, growth hormone and cortisol) were assessed. RESULTS: The two groups did not differ in age, weight or BMI. There were more male participants and individuals with pancreatic exocrine insufficiency in the hypoglycaemia group. Fasting plasma glucose did not differ between the two groups (5.3±0.16 vs 5.3±0.10 mmol/1). Both fasting insulin (20.7±2.9 vs 36.5±4.8 pmol/1; p=0.009) and C-peptide (0.38±0.03 vs 0.56±0.05 nmol/1; p=0.002) were lower in those who experienced hypoglycaemia. Following glucose ingestion, glucose concentrations were significantly lower in the hypoglycaemia group from 135 min onwards, with a nadir of 3.2±0.2 vs 4.8±0.3 mmol/1 at 180 min (p<0.001). The test was terminated early in three participants because of a glucose level <2.5 mmol/1. Insulin and C-peptide concentrations were also lower in the hypoglycaemia group, while incretin hormone responses were not different. Modelling demonstrated that those experiencing hypoglycaemia were more insulin sensitive (439±17.3 vs 398±13.1 ml min(−1) m(−2), p=0.074 based on values until 120 min [n=14]; 512±18.9 vs 438±15.5 ml min(−1) m(−2), p=0.006 based on values until 180 min [n=11]). In line with their better insulin sensitivity, those experiencing hypoglycaemia had lower insulin secretion rates (ISR(fasting): 50.8±3.2 vs 74.0±5.9 pmol min(−1) m(−2), p=0.002; ISR(OGTT): 44.9±5.0 vs 63.4±5.2 nmol/m(2), p=0.018) and beta cell glucose sensitivity (47.4±4.5 vs 79.2±7.5 pmol min(−1) m(−2) [mmol/1](−1), p=0.001). Despite the difference in glucose concentrations, there were no significant increases in glucagon, noradrenaline, cortisol or growth hormone levels. Adrenaline increased by only 66% and 61% above baseline at 165 and 180 min when glucose concentrations were 3.8±0.2 and 3.2±0.2 mmol/1, respectively. CONCLUSIONS/INTERPRETATION: Hypoglycaemia occurring late during an OGTT in people with CF was not associated with the expected counterregulatory hormone response, which may be a consequence of more advanced pancreatic dysfunction/destruction.